Study of 1-(2-hydroxyethyle) 3-methylimidazolium halide as thermodynamic inhibitors - Nashed, O. (Trans Tech Publications Ltd, 2014)
In this study, the performance of 1-(2-Hydroxyethyle) 3-methylimidazolium chloride OH-EMIMCl and 1-(2-Hydroxyethyle) 3-methylimidazolium bromide OH-EMIMBr was investigated as thermodynamic gas hydrate inhibitors. The dissociation temperature was determined for methane gas hydrates using a high pressure micro deferential scanning calorimeter at a pressure range of 36-97 bar. Both ionic liquids (ILs) were studied at concentrations of 5, 10, 15, 20 and 25 wt% then their performance was compared with commercially available inhibitors. It was observed that both ILs shift the methane hydrate equilibrium curve to lower temperature and higher pressure; and the performance of OH-EMIMCl is better than OH-EMIMBr. Nevertheless both of them were found to be less effective compared to methanol and mono ethylene glycol. Â© 2014 Trans Tech Publications, Switzerland.